Natural Abduction: the Bridge between Individuals Choices and the Production of Evolutionary Innovations - Andrade, Eugenio (Signs - International Journal of Semiotics, 2011)
Defenders of developmental systems theory have shown the need for a new evolutionary synthesis. However this effort requires a metaphysical evolutionary framework in which such an expanded synthesis can be embedded. I propose to develop a Peircean monist ontology by explaining the six characteristics or facets of reality labeled as: A) spontaneity, B) determinism, C) processing of information, D) statistical law, E) internally driven capricious choices and F) tendency to form habits. A special emphasis will be dedicated to characterize the predicates C and E as they provide the clue to the understanding of nature as a continuously open-ended and unpredictable process, where its inherent creativity is analogized to an abductive inference.